2016
DOI: 10.1097/mao.0000000000001126
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Superior Canal Dehiscence Surface Area With Vestibular Evoked Myogenic Potentials, Audiometric Thresholds, and Dizziness Handicap

Abstract: Objective To correlate objective measures of vestibular and audiometric function as well as subjective measures of dizziness handicap with the surface area of the superior canal dehiscence (SCD) Study Design Retrospective chart review and radiological analysis Setting Single tertiary academic referral center Patients Preoperative CT imaging, patient survey, audiometric thresholds, and VEMP testing in patients with confirmed SCD Intervention(s) Image analysis techniques were developed to measure the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
5
17
0
1
Order By: Relevance
“…The ABG in Figure 5C show a monotonic increase with increasing size of the dehiscence at frequencies below 1 kHz. This is in line with reports from clinical and experimental studies ( 14 , 46 , 47 ). Hunter et al ( 46 ) computed the correlation between dehiscence size and ABG at 500 Hz and reported it to be r = 0.27.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The ABG in Figure 5C show a monotonic increase with increasing size of the dehiscence at frequencies below 1 kHz. This is in line with reports from clinical and experimental studies ( 14 , 46 , 47 ). Hunter et al ( 46 ) computed the correlation between dehiscence size and ABG at 500 Hz and reported it to be r = 0.27.…”
Section: Discussionsupporting
confidence: 93%
“…The simulations were done for a dehiscence area of up to 6 mm 2 . The limitation to 6 mm 2 was based on the study by Hunter et al ( 46 ) that reported most dehiscence areas to be 6 mm 2 or smaller, with mean areas in different studies ranging from 1.44 to 3.19 mm 2 . The ABG in Figure 5C show a monotonic increase with increasing size of the dehiscence at frequencies below 1 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…Future research is needed to examine the impact of the size of the dehiscence on the oVEMP response with the belly-tendon electrode montage. Hunter et al (2016) found a significant interaction of oVEMP amplitude and the size of the dehiscence when the response was measured with the infraorbital electrode montage (i.e., the oVEMP amplitude increased as the size of the dehiscence increased). In this regard, in cases of smaller dehiscence, the bellytendon montage may offer a higher sensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…Although the gold standard confirmatory test is a high-resolution computed tomography (CT) scan with fine cuts, audiological tests can be used to corroborate the presence of SCDS and to evaluate if the SCDS is active and symptomatic. To date, pure-tone audiometry and vestibular evoked myogenic potential testing (VEMPs) have been shown to be clinically useful in this population (Brantberg et al, 1999;Belden et al, 2003;Hunter et al, 2016). Both the sensitivity and specificity of the ocular VEMP (oVEMP) and cervical VEMP (cVEMP) have been investigated for identifying SCDS (Zuniga et al, 2013).…”
mentioning
confidence: 99%
“…Hinweise für ein Dehiszenzsyndrom ergeben sich, wenn verminderte VEMP-Schwellen bei der Luftleitungsstimulation mit 500 Hz sowie erhöhte VEMP-Amplituden nachweisbar sind [217]. Hunter et al wiesen nach, dass cVEMP und oVEMP-Amplituden und cVEMP-Schwellen mit dem Ausmaß einer Dehiszenz korrelieren [218]. Nach Brantberg und Verrecchia ist bei einem klinischen Verdacht auf ein Dehiszenzsyndrom die Stimulation mit 90 dB nHL ausreichend [219].…”
Section: Vemp In Der Klinischen Praxisunclassified